Soil chemical properties and nitrogen-use efficiency as affected by different sources and nitrogen application schedules under zero-tillage wheat (Triticum aestivum L.) in Haryana - Mohammad Rafi Sangeen,; R.D. Jat,; Ram Swaroop Dadrwal,; Kautilya Chaudhary,; Belal Ahmad Mujahed, (Annals of Agricultural Research, 2025)
Low nutrient use efficiency ( 40%) and environmental pollution due to improper fertilizer management and heavy tillage are the biggest problems in current world agriculture. Thus, for the solution of these challenges, a two-year field experiment was carried out during Rabi season of (2022-23 and 2023-24) in Chaudhary Charan Singh Haryana Agricultural University, Hisar (India) to study the effect of different sources and nitrogen application times on soil chemical properties and nutrient use efficiency. Five different N doses in the main plots and four different N application times in the sub plots have been laid out in the split plot design for the analysis of data. The result of data revealed that application of 100% nitrogen through urea significantly resulted higher available nutrients in soil and higher nutrient use efficiency followed by the application of 75% recommended nitrogen through urea and 25% through nano urea in both respective years. On the other hand, application of nitrogen in three equal split doses (1/3 as basal + 1/ 3 after 1st irrigation + 1/3 after 2nd irrigation) recorded significantly higher nutrient use efficiency and being at par with application of N (1/3 as basal +1/3 before 1st irrigation +1/3 before 2nd irrigation), while soil available NPK and OC did not show any significant difference among different N application schedules during both consecutive years.